2018
DOI: 10.1039/c8nr07755j
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of fluorescently labeled lipids from liposomes in biological environments challenges the interpretation of uptake studies

Abstract: Many commonly used fluorescently labeled lipids were found to dissociate from liposomes during incubation in blood plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 37 publications
3
63
0
3
Order By: Relevance
“…We confirmed that DiI was stably incorporated into the lipid-based NPs (Supplementary Information Fig. S1), as consistent with previous studies using similar types of fluorophores 15,18 . We emphasize that all the lipid-based NPs were prepared with equal mol% of fluorophores (0.5% DiI), and that the concentration of the NPs was adjusted such that the amount of fluorophores (based on absorbance) was equal in each sample (Supplementary Information Fig.…”
Section: Preparation and Characterization Of The Npssupporting
confidence: 91%
See 2 more Smart Citations
“…We confirmed that DiI was stably incorporated into the lipid-based NPs (Supplementary Information Fig. S1), as consistent with previous studies using similar types of fluorophores 15,18 . We emphasize that all the lipid-based NPs were prepared with equal mol% of fluorophores (0.5% DiI), and that the concentration of the NPs was adjusted such that the amount of fluorophores (based on absorbance) was equal in each sample (Supplementary Information Fig.…”
Section: Preparation and Characterization Of The Npssupporting
confidence: 91%
“…The used gains are listed for each NP. The method is similar to what have been described elsewhere 15,18,58 . The DiI seems relatively stably incorporated.…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have demonstrated that up to 75% of such dyes dissociated from vesicles, when incubated in plasma. 53,54 In addition, these commonly used dyes can spontaneously form EVlike particles. 54 Radiolabeling of exosomes presents an alternative imaging strategy; however, few published reports have investigated the biodistribution of postinserted radiolabeled EVs.…”
Section: Mex Biodistributionmentioning
confidence: 99%
“…53,54 In addition, these commonly used dyes can spontaneously form EVlike particles. 54 Radiolabeling of exosomes presents an alternative imaging strategy; however, few published reports have investigated the biodistribution of postinserted radiolabeled EVs. 55,56 An alternative labeling method of engineering MEX with Cre-recombinase in Lox reporter mice has been reported, but it remains unclear whether such engineering methods modulate the functions of the resulting vesicles.…”
Section: Mex Biodistributionmentioning
confidence: 99%